Pengaruh Kepercayaan dan Kepuasan terhadap Loyalitas Pelanggan pada Pengguna Marketplace Shopee - Dimas Yogi Setiawan; Nanda Panji Widiyanto; Bahtari Tiara Amedia; Nindya Kartika Kusmayati (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Factors that can influence customer loyalty are customer trust and satisfaction when shopping at Shopee. Shopee carries out an online marketing strategy by providing several promotional programs for customers, for example vouchers, free shipping, flash sales and cashback. Good experiences received by consumers will foster trust, if this continues, it will lead to satisfaction which will build customer loyalty. The aim of this research is to find out and analyze how much influence trust and satisfaction have on customer loyalty among Shopee marketplace users, both partially and simultaneously. The research was carried out using quantitative methods, as well as a causal relationship research design. The sample method was nonprobability sampling with purposive sampling, using SPSS version 23 software. The sample in this study was 80 respondents. The analytical method used is multiple linear regression analysis. The research results prove that the t test shows that the trust variable has a positive and significant effect on customer loyalty. And the satisfaction variable has a positive and significant effect on customer loyalty. Based on the results of the f test, it can be concluded that the variables of trust and satisfaction simultaneously have a positive and significant effect on customer loyalty.